The ultimate book of big cats : your guide to the secret lives of these fierce, fabulous felines - Winter, Steve; Guynup, Sharon (Washington, D.C. : National Geographic Kids, 2022)
"A LEOPARD LEAPS into a tree with prey twice its weight. A LION lets out a ROAR and lunges at a wildebeest across the golden plains. A JAGUAR silently STALKS a deer through the dense, dark jungle. Through famed National Geographic photographer Steve Winter's legendary, award-winning lens, readers will get up close and personal with the "big four"--lions, tigers, jaguars, and leopards--presented against their stunning natural landscapes, and go beyond to explore other show-stopping wild cats like snow leopards, cheetahs.
The super seven -- Big cats inside and out -- When big cats were cubs -- Hunt, eat, sleep -- In cat territory -- Ancient cats -- Challenges facing big cats -- Be a big cat defender.
Includes index.
3-6
6.9
Keywords: Panthera -- Juvenile literature; Felidae -- Juvenile literature; Cats -- Juvenile literature; Cat family (Mammals)